COMPARATIVE STUDY OF THE COMPOSITION OF THE NEUROLEPTIC SYNDROME IN PATIENTS WITH SCHIZOPHRENIA - Zokirov M. M. (Web of Journals Publishing, 2024)
The aim of the study is to compare the side effects of typical and atypical neuroleptics in patients with schizophrenia. The study included 60 patients, divided into three groups: haloperidol, clozapine, and risperidone. Side effects were assessed using ESRS, SAS, UKU scales and body mass index changes. Galoperidol was more likely to cause extrapyramidal disorders, sedative effects, and sexual dysfunction. Atypical neuroleptics, especially risperidone, rarely caused extrapyramidal symptoms, but were associated with increased body weight and hyperprolactinemia. Atypical drugs showed better tolerance and are preferred for long-term therapy.